The Potential of Onggok Starch Waste in Daleman Village, Tulung District, Klaten Regency and its Management as a Biotechnology Learning Resource - Erna Noor Savitri; Margareta Rahayuningsih; Aditya Marianti (Universitas Negeri Semarang, 2024)
This research examines the presence of onggok starch waste in Daleman Village, Tulung District, Klaten Regency and the handling efforts that have been carried out. The existence of waste and efforts to handle it can potentially be used as a learning resource in biotechnology and bioenergy lectures. This research uses a descriptive qualitative approach. Data was collected through observation, interviews, documentation and literature study. The results of this research show that people in Daleman Village, Tulung District, Klaten Regency have a household scale business in the form of making starch flour which will be used as an ingredient for making noodles, cendol and other processed foods. Until now, many efforts have been made to process this waste, but have not produced optimal results. Based on the results of scientific studies, it was found that onggok starch waste can be processed and processed into biogas and briquettes so that it can be used as a student learning resource to foster students' environmental ethics.